Expression Profile of Multidrug Resistance Efflux Pumps During Intracellular Life of Adherent-Invasive Escherichia coli Strain LF82 - Fanelli, Giulia; Pasqua, Martina; Colonna, Bianca; Prosseda, Gianni; Grossi, Milena (Frontiers in Microbiology, 2020)
Efflux pumps are present in all living cells and represent a large and important group of transmembrane proteins involved in transport processes. Over the years studies on the role of efflux pumps in bacteria have been mainly centered on the capability of these membrane complexes to export one or more antibiotics. Multidrug resistance (MDR) efflux pumps confer resistance to antibiotics at different levels and are deeply implicated in the fast and dramatic emergence of antibiotic resistance. Recently, several reports have outlined the great versatility of MDR efflux pumps in exporting a large variety of compounds other than antibiotics, thus contributing to bacterial adaptation to a wide range of habitats. In several bacterial pathogens MDR efflux pumps contribute to increase the virulence potential and are directly involved in the crosstalk with host cells. In this work we have investigated the possible contribution of MDR efflux pumps to the infectious process of the Adherent-Invasive Escherichia coli (AIEC), a group of pathogenic E.coli that colonize the ileal mucosa of Crohn’s disease patients. AIEC are able to adhere to and invade intestinal epithelial cells, to survive within macrophages and to cause a strong intestinal inflammation. The results we have obtained indicate that, with the exception of mdtM, all MDR-efflux pumps encoding genes present in E.coli K12 are conserved in the AIEC prototype strain LF82. The analysis of the MDR efflux pump expression during LF82 infection of macrophages and epithelial cells reveals that their transcription is highly modulated during the diverse steps of the bacterial intracellular life, with some EP genes being regulated in a cell type specific manner. Finally, we present evidence indicating that MdtEF, an MDR EP belonging to the RND family, significantly contributes to bacterial fitness in macrophage environment.